Functionalization of Frustules of the Diatom Staurosirella pinnata for Nickel (Ni) Adsorption From Contaminated Aqueous Solutions - Savio, Saverio; Farrotti, Serena; Di Giulio, Andrea; De Santis, Serena; Ellwood, Neil Thomas William; Ceschin, Simona; Congestri, Roberta (Frontiers in Marine Science, 2022)
The structural characteristics of diatom cell walls (frustules) has led to their widespread use in diverse biotechnological applications, some of which can be further improved by surface chemical modification (functionalization). The use of coating agents can significantly increase surface binding capacity for target compounds. Frustules of the diatom Staurosirella pinnata used here were a by-product after applying a cascade-extraction process (for other products) to mass cultures. The protocol for the cleaning and functionalization of raw frustules using 3-Mercaptopropyl-trimethoxysilane and 3-Aminopropyl-trimethoxysilane was optimized and reported. Functionalization efficacy was observed using Electron Microscopy, Energy Dispersive X-ray Spectroscopy and Fourier-Transform Infrared Spectroscopy. Optimally functionalized frustules were evaluated for nickel removal from aqueous solutions. Incubations of 10 min, using 1 g/L of frustules, gave almost complete Ni removal with functionalized frustules compared to 3% removal by raw frustules. The proposed protocol represents a reproducible and efficient alternative for Ni removal from contaminated water.